Aspects of forest management in the maintaining of forest environment = Urządzeniowe aspekty kształtowania środowiska leśnego - Jaszczak, Roman; Gołojuch, Piotr; Wajchman-Świtalska, Sandra; Miotke, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Forest management is a scientific discipline designed to develop methods of maintaining forest areas and to ensure the sustainable development of forest resources in terms and conditions of multifunctional forestry. This is a branch of practical forestry which deals with inventorying and assessing the state of forests, defines economic tasks and draws up a program of nature conservation for forest districts.
Keywords: forest; forest management plan; objectives of forest management; legal basis; las; plan urządzenia lasu; gospodarka leśna; podstawy prawne gospodarki leśnej